Significance of Exponential Space-Based Internal Heat Source on Bio-Convective Maxwell Nanofluid Flow Due to Stretching Sheet in the Presence of Darcy–Forchheimer and Lorentz Forces - Arbaz, Muhammad; Azam, Muhammad Khurshid; Imran, Muhammad (Scientific Inquiry and Review, 2026)
This study investigates two-dimensional flow of bio-convective Maxwell nanofluid over a stretching sheet in the influence of motile microorganisms. Furthermore, the impact of thermal radiation and exponential space-based heat sources have been analyzed. The results showed that magnetic, Darcy–Forchheimer, Deborah and inertia parameters significantly suppressed the velocity field while modifying thermal and concentration boundary-layer thicknesses. Brownian motion and thermophoretic effects enhanced temperature and nanoparticle concentration, whereas bioconvective parameters strongly regulated microorganism density and associated bio-convective patterns. Applications of the current research study include model oil reservoirs, solar energy technology, re-entry of spacecraft, electrical power generation, cosmological flows, chemical engineering, air and water management systems, industrial zones, human blood flow, bioindustrial systems, environmental sciences and power generating systems, etc.